SOCIAL CARRYING CAPACITY AS A FRAMEWORK FOR CONTROLLING THE SOCIAL IMPACTS OF TOURISM: A CASE STUDY OF SERANGAN VILLAGE, BALI - Yopi Maulana; Feronika Berutu; Yoshie Sukendar Anwar; Arief Faizal Rachman (International Journal of Social Science, 2025)
In the development of sustainable tourism, careful planning and comprehensive management are critical issues, particularly in relation to the potential social impacts arising from tourism activities. Tourists bring their cultures, values, and behaviors into local communities, inevitably influencing the social and economic life of the residents. To minimize these potential impacts, an effective management framework is required. One such framework is the concept of social carrying capacity, which serves not only as a measure of the optimal utilization of resources and tourism activities but also as a guideline for determining the maximum level of interaction and participation between local communities and tourists within a destination area.This study adopts a qualitative descriptive approach using a case study method focused on Serangan Village, Bali. Data were collected through in-depth interviews, direct observation, and documentation to analyze how tourism development and reclamation have affected social life and community behavior. The analysis was conducted descriptively to explore how social carrying capacity can function as a framework for controlling the social impacts of tourism. The findings are expected to contribute to the formulation of community-based tourism management strategies that promote social balance and sustainability in tourist destinations